1996
DOI: 10.1016/s0748-7983(96)90671-x
|View full text |Cite
|
Sign up to set email alerts
|

Isolated limb perfusion with TNFα and melphalan in a rat osteosarcoma model: a new anti-tumour approach

Abstract: Isolated limb perfusion (ILP) with TNF alpha, IFN gamma and melphalan causes impressive tumour reduction in patients with irresectable soft tissue sarcomas with a high limb salvage rate. Since this therapy could be of value in patients with progressive osteosarcoma, we performed a study in an osteosarcoma tumour model in the rat. The ROS-1 osteosarcoma was implanted s.c. in the hind leg of WAG rats. Rats were divided in four groups: rats that underwent ILP with perfusate alone, TNF alpha alone, melphalan alone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 20 publications
2
22
0
Order By: Relevance
“…Several laboratories have recently reported, however, promising data utilizing TNF in limb perfusion studies which limit systemic exposure. 22,[26][27][28][29][30][31][32][33] Consequently, coupling TNF expression to a replicationselective Ad should limit its expression to the infected tumor, reducing systemic toxicity and increasing its therapeutic effectiveness alone or in combination therapies.…”
Section: Figure 1 Diagram Of Ad5 E3 Region Depicting Transgene Insertmentioning
confidence: 99%
“…Several laboratories have recently reported, however, promising data utilizing TNF in limb perfusion studies which limit systemic exposure. 22,[26][27][28][29][30][31][32][33] Consequently, coupling TNF expression to a replicationselective Ad should limit its expression to the infected tumor, reducing systemic toxicity and increasing its therapeutic effectiveness alone or in combination therapies.…”
Section: Figure 1 Diagram Of Ad5 E3 Region Depicting Transgene Insertmentioning
confidence: 99%
“…Isolated perfusion with tumour necrosis factor-α in combination with ischaemia (Manusama et al, 1994) or with melphalan (Manusama et al, 1996a(Manusama et al, , 1996b has been reported to result in complete tumour regression in preclinical tumour models. Isolated limb perfusion in patients with in-transit melanoma with TNF-α in combination with melphalan and γ-interferon resulted in high complete remission rates (LiŽnard et al, 1992(LiŽnard et al, , 1994.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,9 In our laboratory, Manusama et al 7 modified the technique of ILP in rats, originally described by Benckhuijsen et al 10 In this model, by using the BN-175 soft tissue sarcoma, it was shown that only when TNF was combined with melphalan or doxorubicin could a tumor response be reached. In comparison to the clinical setting, our rat model demonstrated partial or complete regression of the tumor in approximately 75% of rats receiving an ILP with melphalan plus TNF.…”
Section: Ilp Modelmentioning
confidence: 99%